An Integrated Management of Type-2 Diabetes Mellitus associated with Hypertension and Dyslipidemia with Naturopathy and Yoga: A Case Report - Singh, Poonam (International Research Journal of Ayurveda & Yoga, 2023)
The whole practice of nature cure is based on the following three principles: Accumulation of morbid matter, the abnormal composition of blood & lymph lowered vitality. Nature cure believes that all diseases arise due to the accumulation of morbid matter in the body and if the scope is given for its removal, it provides a cure or relief. It is believed that the human body possesses inherent self-constructing and self-healing powers. The blood pressure and blood sugar significantly reduce and the lipid profile also improves due to the influence of yoga practices and naturopathic management. Lifestyle is an important risk factor for increasing the prevalence of diabetes in the Indian population. In this study, we evaluated the effects of naturopathy treatment, salt-restricted low calorie diets, and yoga in long-term glycemic control in patients with type 2 diabetes mellitus.